(3eLGdS GdThQi aj YUQ SdGWjf GdeeGdjc (B(648-923(3g`(B/1250-1517(3e(B)s - (3YWG,YKeGf Ydjs; (3SejQ (B, (3gfOs (3JUeje GdZdGas ((3GdbGgQIs (3GdgjFI GdeUQjI GdYGeI ddcJGHs, 2021)
(3jcTa ajg cja cGfJ oJOGQ MQhH GdYQH VqO GdZRh GdCLfHj aj Jdc GdaJQI, eDckOG Cf eLGdS GdeThQI dYHJ OhkQG HGQkRG, Ydi eOGQ GdJGQjpN GdYQHj GdESdGejs
Keywords: (3GdgjFGJ GdJTQjYjIs; (3OhdI GdeeGdjcs; (3eLdS GdThQis; (3GdYGde GdYQHjs -- (3JGQjNs -- (3YUQ GdeeGdjcs